Proses Pengakuan Khonghucu Pada Masa Pemerintahan Abdurrahman Wahid (2000-2001) - Mustofa Maulid; Samsudin Samsudin; Dina Marliana (UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study was to determine the condition of the Confucian religion in Indonesia after its legality was recognized by the government, especially during the reign of K.H. Abdurrahman Wahid. In addition, it is also to find out how the process of establishing the Confucian religion so that it can become an official religion in Indonesia. The method used in this research is the historical research method, which is a research model of events or incidents in the past based on the traces left behind. This research method was carried out through four stages, namely; Heuristics, Criticism, Interpretation and Historiography. Based on the results of the formulation of the research problem, it can be concluded that first, starting in 2000 in Indonesia there was no longer the term religion recognized by the government or religion that was not recognized by the government so that the condition of the Confucian religion at that time was in a safe position and began to be able to express itself independently open to worship and perform holidays. Second, After K.H. Abdurrahman Wahid occupied the presidency in 1999. In 2000 he issued a policy by revoking Inpres No. 6 of 1967 and the Circular of the Minister of Home Affairs No. 477/74054 / BA.01.2 / 4683/95 of 1978 concerning the limitation of Chinese religious activities, beliefs and customs, with the issuance of Presidential Decree No. 06 of 2000. The elimination of the term official religion recognized by the government which is based on the principles of Pancasila and the 1945 Constitution Article 29 paragraph 1 and 2. With the policies carried out by Gus Dur it becomes a policy tap on Confucianism for the next government. Keywords: Abdurrahman Wahid, Policy, Confucianism